Determiner Phrase in Persian - reza sahraei (Matn/Pizhūhī-i Adabī, 2010)
Surveying the structure of NP in Persian, this study tries to show that most of NP constituents are either independent of each other or they are dependent to Determiner Phrase (=DP). The researcher follows a uniform minimal analysis to illustrate the structural position of relevant constituents of DP, including Possessive Phrase, Prepositional Phrase and Quantifier Phrase, under the tree diagram. The most important point of this study is the claim that NP is mostly one of the dependents of DP. Hence, the final section of the study deals with and analyzes the structure of DP in Persian. The DP analysis undertaken in this study has some advantages. It can explain the internal relevance of all DP constituents and provides them all with a uniform analysis. Likewise, the semantic importance of Persian genitive marker and its role in parsing are borne out.